Assessment of Organochlorine pesticides in cocoa beans from Ashanti and Brong Ahafo regions of Ghana - S, Boakye,; Essien W, Jonfia-; B.R, Voegborlo,; N,O, Boadi (IJRDO-Journal of Applied Science, 2016)
Research was conducted in the Ashanti and Brong Ahafo regions of Ghana to determine organochlorine pesticide residues in cocoa beans. The pesticides were extracted by using solvent extraction technique followed by clean up with C-18 and Envi – Carb NH2 solid-phase extraction cartridges. Extracts were dissolved in ethyl acetate and analysis carried out by Gas Chromatograph equipped with Electron Capture Detector. Retention times were used for identification of pesticides and quantified using external calibration method. From this study, 55.5 % of cocoa beans sampled from Brong Ahafo region and 66.7 % of cocoa beans sampled from the Ashanti region had organochlorine pesticide residue concentrations above the EU permissible levels. Heptachlor had the maximum concentration of residues whilst heptachlor exo epoxide had the minimum concentration for the two regions. The results obtained reflect the enormous past use and continual usage of pesticides on cocoa beans in Ghana.